Rozum versus (u)czucie. Filozofii krytycznej z (neo)platonizmem przypadki (kilka słów od tłumacza) - Artur Banaszkiewicz (Hybris, 2021)
The following paper provides a historical and biographical introduction to the reading of the translation of Kant’s essay Von einem neuerdings erhobenen vornehmen Ton in der Philosophie. It consists of three parts. In the first one, called Introductory remarks, I point out the specific role of Kant’s polemical writings in his work. In the second, Protagonists, I outline the biographies of both of Kant’s opponents: J. G. Schlosser and Friedrich Leopold Graf zu Stolberg-Stolber. Finally, in the third one, I discuss a number of translation problems with the terms “Ahnung” and “ahnen”.